Natural radioactivity and heavy metal pollutants in staple foodstuff and human teeth collected from selected areas in Peninsular Malaysia / Khandoker Asaduzzaman - Khandoker , Asaduzzaman (2017)
This study is aimed at the evaluation of natural radioactivity (natural decay chains of 238U and 232Th, and non-series long-lived natural radionuclide 40K) and heavy metal (Pb, Cd, As, Hg, Cr, Cu, Sr, Al, Mg, Sb, Ba, Bi, Zn, Rb, Mn and Ni) exposures resulting from the consumption of staple foodstuffs such as rice, vegetables and marine animals. In addition, heavy metal levels in human teeth have been assessed as a bio-indicator of exposure to environmental pollution. The studied samples were collected from different locations across the Peninsular Malaysia. The radioactivity concentrations have been measured by -ray spectrometry using high resolution high purity germanium (HPGe) and scintillation NaI(Tl) detector and the heavy metals were determined by inductively coupled plasma-mass spectrometry (ICP-MS). The results showed that the radioactivity in different varieties of vegetable samples varied from 0.5127Bq kg1 for 226Ra, 0.2143 Bq kg1 for 228Ra (232Th) and 562483 Bq kg1 for 40K. The radioactivity in rice in different areas varied from 1.5±0.42.8±0.7 Bq kg1 for 226Ra, 3.6±1.47.5±2.7 Bq kg1 for 232Th and 59.9±6.092.2±5.4 Bq kg1 for 40K. On the other hand, the activity concentrations of 226Ra, 228Ra and 40K in marine animals varied from 0.6±0.197.83±0.78 Bq kg1, 0.19±0.176.21±0.53 Bq kg1 and 34±13398.6±20.2 Bq kg1, respectively. The estimated soil-to-tapioca, -sweet potato and -rice transfer factors for 226Ra and 232Th were found much higher than the International Atomic Energy Agency (IAEA) reported values. The annual effective dose obtained due to ingestion of radionuclides via the consumption of the studied foodstuffs were found below the world average value (290 μSv y1) and the associated life-time cancer risk were also below the acceptable limit of 103 for radiological risk, thus discarding any significant radiological risks to the population of Peninsular Malaysia. The concentrations of heavy metals (mg kg‒1) in vegetables were found as: Pb (0.0010.006), Hg (0.00190.005), Ni (0.00040.008), Cr (0.00030.006), Al (0.0658.1), Sr (0.010.72), Bi (0.050.80), Sb (0.11.2), Ba (0.0010.034), Rb (0.020.13), Mn (0.0122.1), Zn (0.010.59), Fe (0.051.6), Cu (0.0010.06) and Mg (1.847.0), while in marine fishes were found as: As (0.32490.7485), Pb (0.02), Hg (0.0247), Al (3.1154.489), Cr (0.01080.0516), Sr (19.5627.68), Co (0.00070.0038), Cu (0.07120.1972), Mn (0.43721.841), Zn (5.60715.35), Fe (3.5464.857), Rb (0.09780.2312), Ba (0.28450.6597), Bi (1.5984.143) and Mg (80.43115.0). The concentrations of all the studied heavy metal in vegetables and fishes were below the daily limit on intake recommended by the international organizations, indicating yet pose no threat to public health. Conversely, trace amount of heavy metals were found in almost all teeth samples. Increased accumulation of Pb, Hg, As, Cr, Mn, Sr, Ba, Sb, Cu, Zn, Mg and Sn in teeth dentin was observed with respect to the teeth age. Some elevated levels of concentrations of heavy metals in the teeth dentin reflect the relation to pollution from industrial emissions and urbanization. Human teeth dentin, therefore, can be used as reliable bio-indicator of environmental pollution by heavy metals. Since higher concentration of radioactive- and heavy metal substances in the environment is undesirable, continuous monitoring should be undertaken to detect the concentration of radioactive and heavy metals in foodstuffs in order to take necessary radiological and dosimetric measures with the aim of minimizing the potential harmful effects of ionizing radiation.